La motivación y su incidencia en el rendimiento académico de los alumnos de primer y segundo año de bachillerato de la asignatura de proceso contables especialización contabilidad de la Unidad Educativa Emigdio Esparza Moreno de la Ciudad de Babahoyo, Provincia de los Ríos - Moreira Engracia, Candy Katherine (2014)
This thesis aims to point out what the effects of motivation are academic performance of students in first and second baccalaureate accounting specialization Education Unit “Emigdio Esparza Moreno " in the city of Babahoyo , Los Ríos Province in the period school from 2014 to 2015. The study considering the problem of low motivation in learning, foundations and matrix independent and dependent variables is done, a survey was applied to teachers and an observation to the class of children, conducting analysis and interpretation of results, the same can be concluded that the majority of teachers agree that motivation is important for meaningful learning, why worry to motivate children, a good motivation in different spheres for help side to improve learning. It was considered some definitions and background that supported to increase knowledge on the subject, with the help of technical and scientific support, without forgetting that the timely and proper motivation allow better development of the learning process. The project proposes an innovative and committed approach to the educational action that involves designing a teaching guide with motivational strategies to be implemented in the first year of Basic Education